The Reasons Behind a Career Change Through Vocational Education and Training - Masdonati, Jonas; Fournier, Geneviève; Lahrizi, Imane Zineb (International Journal for Research in Vocational Education and Training, 2017)
We report the results of qualitative research on adults who enrolled in a vocational and education training (VET) program with the intention of changing their careers. The participants were 30 adults aged between 25 and 45 years. A modified version of the consensual qualitative research method was applied to transcriptions of semi-structured interviews with the participants. There appeared to be two main reasons underlying the decision to enrol in a VET program with the aim of initiating a career change. Based on the reasons given, two groups (career changers and proactive changers) and five distinct categories were recognized. The career changers included individuals who wished to change careers due to dissatisfaction with their current situation. In this group, the decisions were motivated by either health problems or personal dissatisfaction. The proactive changers included individuals who wished to reorient their career because of a desire to undertake new projects. In this group, there were three categories of reasons: a wish to attain better working conditions, a search for personal growth and a desire to have an occupation that fitted the person’s vocation. Thus, the participants reoriented their careers according to various motivations, pointing to the existence of a heterogeneous population and the complexity of the phenomenon. The results highlight the importance of understanding the subjective reasons behind career changes and the need to adjust career interventions accordingly.